Practical system reliability - 497990 Bauer, Eric; Zhang, Xuemei; Kimber, Douglas A. (Piscataway, NJ : IEEE Press ; Hoboken, NJ : Wiley, 2009)
Includes bibliographical references (p. 265-277) and index